Pelatihan Strategi E-Commerce Dalam Mengembangkan Keunggulan Daya Saing Produk Usaha bagi Pelaku Bisnis UMKM Kota Bandung - Cucu Hodijah; Hasti Pramesti Kusnara; Umban Adi Jaya (Jurnal Pengabdian UNDIKMA, 2023)
This service aims to enhance the competitive advantage of MSMEs in the global market through the implementation of e-commerce strategies. The community engagement activity involved 37 registered MSME participants. The training was delivered in the form of interactive learning sessions, covering topics such as e-commerce introduction, digital marketing strategies, the use of social media, marketplaces, and market analysis. The evaluation was conducted by distributing satisfaction questionnaires to participants and then analyzed descriptively. The results demonstrated significant benefits of the e-commerce training for the MSME participants. The participants showed an improved understanding of e-commerce and effective ways to utilize it for product marketing and customer interaction. The majority of participants expressed satisfaction with the training content and methodology.